2021
DOI: 10.1051/0004-6361/202037861
|View full text |Cite
|
Sign up to set email alerts
|

The OTELO survey as a morphological probe. Last ten Gyr of galaxy evolution

Abstract: Context. The morphology of galaxies provide us with a unique tool for relating and understanding other physical properties and their changes over the course of cosmic time. It is only recently that we have been afforded access to a wealth of data for an unprecedented number galaxies thanks to large and deep surveys. Aims. We present the morphological catalogue of the OTELO survey galaxies detected with the Hubble Space Telescope (HST)-ACS F814W images. We explore various methods applied in previous works to se… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 70 publications
1
6
0
Order By: Relevance
“…Extending the pioneering work of Lilly et al (1998) and including a treatment to convert surface brightness into mass surface density, Barden et al (2005) found evidence for a non-evolving mass-size relation (𝛽 𝑧 = 0) since 𝑧 = 1 (though note that van der Wel et al 2014 associates a small but non-vanishing 𝛽 𝑧 = 0.2 to the same work). A similarly small value 𝛽 𝑧 = 0.17 can be derived from the more recent results of Barone et al (2021) in the redshift range 0.014 < 𝑧 < 0.76, while Nadolny et al (2021) found statistically insignificant evolution since 𝑧 ∼ 1.5 (see also Nagy et al 2011, who found 𝛽 𝑧 = 1.42 for 𝑧 > 1.5 and predicted convergence to the local relation by 𝑧 ∼ 1). Perhaps unsurprisingly, studies involving intermediate baselines 0.2 𝑧 2.5 find intermediate values 𝛽 𝑧 ∼ 0.75 (van der Wel et al 2014;Paulino-Afonso et al 2017).…”
Section: Is the Mass-size Relation Evolving With Time?supporting
confidence: 65%
See 1 more Smart Citation
“…Extending the pioneering work of Lilly et al (1998) and including a treatment to convert surface brightness into mass surface density, Barden et al (2005) found evidence for a non-evolving mass-size relation (𝛽 𝑧 = 0) since 𝑧 = 1 (though note that van der Wel et al 2014 associates a small but non-vanishing 𝛽 𝑧 = 0.2 to the same work). A similarly small value 𝛽 𝑧 = 0.17 can be derived from the more recent results of Barone et al (2021) in the redshift range 0.014 < 𝑧 < 0.76, while Nadolny et al (2021) found statistically insignificant evolution since 𝑧 ∼ 1.5 (see also Nagy et al 2011, who found 𝛽 𝑧 = 1.42 for 𝑧 > 1.5 and predicted convergence to the local relation by 𝑧 ∼ 1). Perhaps unsurprisingly, studies involving intermediate baselines 0.2 𝑧 2.5 find intermediate values 𝛽 𝑧 ∼ 0.75 (van der Wel et al 2014;Paulino-Afonso et al 2017).…”
Section: Is the Mass-size Relation Evolving With Time?supporting
confidence: 65%
“…Mowla et al 2019Nedkova et al 2021) and some others finding little or no evolution out to 𝑧 1.5 (e.g. Nadolny et al 2021). In addition to the considerations above, uncertainties in the recent evolution may also be related to the fact that, when directly comparing observed sizes at different redshifts, a small redshift leverage also implies that variations may become subtle to discern (e.g.…”
Section: Evolution Of the Mass-size Relationmentioning
confidence: 99%
“…The OTELO catalog includes OTELO detections and reprocessed ancillary data from Chandra, GALEX, CFHT, WIRDS, and IRAC covering from ultraviolet to the mid-infrared. Our sample consists of 370 OTELO galaxies included in the Nadolny et al (2021) morphological analysis, of which 31 are early-type and 339 latetype. All these galaxies have spectral redshift z < 1.41 obtained from the DEEP2 Galaxy Redshift Survey (Newman et al 2013;Bongiovanni et al 2019).…”
Section: Photometric Datamentioning
confidence: 99%
“…Stellar masses (M * ) for the overall OTELO sample were computed from the mass-to-light ratio prescription of López-Sanjuan et al ( 2019) for star-forming galaxies (more details about obtaining stellar masses in the OTELO survey can be found in Nadolny et al (2021). The stellar mass for the Hβ sample is in the range of 10 7.6 < M * < 10 10.7 M .…”
Section: Stellar Masses and Sfrmentioning
confidence: 99%
“…To determine the morphological features of our galaxy sample, we made use of the available 2 HST high-resolution (F606W and F814W) images for a visual morphological classification. The detailed morphological analysis of all OTELO sources up to z = 2 is in the scope of a forthcoming paper (Nadolny et al 2021).…”
Section: Morphologymentioning
confidence: 99%